ANALISIS PERBANDINGAN FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN NASABAH DALAM MEMILIH KPR KONVENSIONAL ATAU KPR SYARIAH - Saminem (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2018)
The purpose of the study is to examine the factors influencing the customer to choose home financing in East Jakarta. Then compare if there are any significant differences between the driving factors influencing the customer in selecting conventional home financing or Islamic home financing. Distributing questionnaires were carried out on respondents to collect the primary data. This data were processed by using Statistical product and Service Solution (SPSS) 20.0 for windows. The indicators were using are the level of awareness, the knowledge of the product, marketing strategy, the perception toward the product, product features, and the service quality. In the analysis using means compare independent sample t-test and discriminant analysis. The finding revealed that there were no significant differences between the driving factor groups of conventional home financing and Islamic home financing. However, in terms of means value there were differences between the two groups. The result showed that the level of awareness of customers in selecting Islamic home financing is higher than conventional home financing (13,56>12.98). Moreover, the knowledge of the product of customers who selecting Islamic home financing is better than conventional home financing (16,08>15,76). While in terms of marketing strategy, the perception toward the product, product features, and the service quality of conventional home financing is superior compare to Islamic home financing.